(3dYH GdTWQfL GdgfOis - (3GddLGL GdTWQfLj , GdeXaQ Hf SYO, CHh GdaQLs
(3ChdgG (B:s
(3hHYO agPg JPcQI YedgG CHh GdaQL GdeXaQ Hf SYO GdeYQha HGddLHdGL GdTWQfLi djYjf GddGYH HGdTWQfL Ydi EUdGM acQg s
(3BNQgG (B:s
(3eKd bjeI GdaQRGf hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3fSNI bOjeI ecJhHI dNRGfI NGfi Hcs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3CdYGH JjehQ (B6) s
Keywords: (3GdTWQfLs